The association between risk factors and the occurrence of retinopathy of prematurity in premature infants: An exploratory study - Vera Sumual; Anugrah Handini Masloman; Salam Surbakti; Angelina Patricia Chandra (Published by Universitas Gadjah Mada, 2026)
Retinopathy of prematurity (ROP) remains a leading cause of preventable childhood blindness. Although gestational age and birth weight are well-established risk factors, the contribution of other clinical factors may vary across settings, particularly in low-and-middle-income countries such as Indonesia. The study aimed to evaluate risk factors associated with the incidence of retinopathy of prematurity, including gestational age, birth weight, duration of oxygen therapy, and infection, in a tertiary-care hospital in Indonesia. This retrospective study reviewed medical records of premature infants with and without ROP at Prof Dr. RD Kandou General Hospital, Manado, Indonesia. Eligible infants underwent initial ophthalmologic examination at or before 1 years old. Data collected included sex, gestational age, birth weight, duration of oxygen therapy, presence of infection or sepsis, and ROP status. Associations were evaluated using Chi-square tests and bivariate logistic regression to estimate crude odds ratios (ORs). Multivariable logistic regression analysis was performed to adjust for potential confounding, with adjusted odds ratios (aORs) and 95% confidence intervals (CIs) reported. Multivariable results were interpreted as exploratory due to the limited number of ROP cases. A total of 51 infants were included, of whom 14 (27.5%) developed ROP. Lower gestational age (≤34 weeks), lower birth weight (≤1500 grams), and oxygen therapy duration ≥1 weeks were significantly associated with ROP in bivariate analyses. After multivariable adjustment, none of the variables remained statistically significant, although the direction of association persisted for gestational age, birth weight, and oxygen therapy. Infection or sepsis was not significantly associated with ROP. In conclusion, lower gestational age, lower birth weight, and prolonged oxygen therapy are associated with an increased incidence of ROP in this cohort. These findings emphasize the importance of targeted screening and careful oxygen management in premature infants. Larger prospective multicenter studies are needed to clarify independent risk factors for ROP in Indonesia.